Registration System with Midtrans Payment Gateway using Waterfall Method - Robby Firmansyah Ardha; Mochamad Alfan Rosid (Procedia of Engineering and Life Science, 2022)
The Airlangga international conference is an event organized by the student executive body of Airlangga University which is engaged in youth for international issues which then comes up with ideas to solve these social issues. To join this activity, you need to fill in your personal data and then upload the article. A registration system that requires a lot of end-user time because it has to go through the admin approval stage manually. The confirmation process that must upload proof of transaction data is quite consuming business processes and involves many actors to provide confirmation to end users. In solving this problem, this research implements a payment gateway as automation in the payment process in the registration information system. This research using the PHP programming language which is integrated with the midtrans payment gateway. This research also uses the waterfall method in the application development process, then the blackbox method for testing and also codeigniter as a framework for development. This registration information system has business processes ranging from creating an account, selecting a category, filling out forms, making payments, and uploading articles. With the implementation of a payment gateway to the information system, it is hoped that it will gain validity in the registration process as well as help ease the burden on the committee in preparing financial reports.